Implementation of Information Technology Systems as a Media for Financial Decision Making at SMAK Framatu Surabaya - Albinus Di; Dionisius Hadun (Applied Business and Administration Journal, 2024)
This study aims to determine the impact of implementing information technology systems as a medium for making financial decisions at SMA Framatu Surabaya. The research method uses field research with observation and interviews. Data analysis technique using quantitative descriptive. The results of the study show that using information technology systems as a medium for making financial decisions will have a positive influence on schools. Where by using information technology systems, schools can obtain financial information accurately, quickly and precisely. The data obtained from the information technology system is used as a medium for making school financial decisions. So that schools can know exactly how much the amount of receipts and expenditures is during one period. On the other hand, this information is also used by schools to control and control operational expenses in order to avoid wasting cash. The impact of managing and controlling cash will make the school's financial balance sheet healthier and better .